Students Perception on the Integration of Task-Based Learning and Dubbing Short Video in Learning Speaking Skill - Helmie, Jauhar; Setiawati, Ghina Salsabila; Salsabila, Vina Aini (Linguistics and ELT Journal, 2024)
This research aims to analyse the students’ perception towards the integration of task-based learning and dubbing short video in learning speaking skills and the difficulties of the integration of task-based learning and dubbing short video in learning speaking skills. This research applies a qualitative approach using observation and questionnaires as instruments to answer the research questions. The subject of this research were the second-year students in SMA Pasundan 1 Cianjur. The findings of this research show that the integration of task-based learning and dubbing video helped the students improve their speaking skills, especially in pronunciation and fluency.  This research also reveals that students (30) enjoyed learning with task-based and dubbing. they also became confident when speaking English. Besides that, students’ editing skills also got better and students became aware of using applications for editing. On the hand, this research found some difficulties faced by the students consisting of the difficulty in pronouncing English words, difficulty in writing the text that will be dubbed, low signal, limited memory, noisy sounds and the difficulty in editing video dubbing and  the groups had difficulty creating the text that would be dubbed and the data from the questionnaire also mention the same things